Hegemoni Adat dan Resistensi Estetis: Analisis Kritis Gaya Bahasa Hamka dalam Merepresentasikan Realitas Matrilinealisme Minangkabau (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The matrilineal kinship system in Minangkabau places women in a highly privileged position as owners of heirlooms and lineage. However, the sociological reality captured in literary works often reveals a flip side, namely the rigidity of customs that restricts individual freedom. This study aims to analyze Hamka's linguistic style in depicting the reality of rigid matrilinealism experienced by female characters in three selected novels: Merantau ke Deli, Di Bawah Lindungan Ka'bah, and Tenggelamnya Kapal Van Der Wijck. This study uses a qualitative descriptive method with content analysis techniques to dissect the intrinsic and extrinsic elements of the works. The results show that Hamka uses a melancholic style of language, natural metaphors, and sharp traditional proverbs to portray the inner suffering of Minang women. In these novels, it is found that although women are honored by customary status, they often become victims of kinship decisions regarding matchmaking and social status. Hamka criticizes the phenomenon of